MECHANICAL-FLUSH CHEMICAL TOILET. - Drobny,Neil L. (1966)
Sanitary facilities normally encountered in the polar regions leave much to be desired. Existing facilities must be improved if a healthy and safe environment is to be provided. Previous studies indicated that the chemical toilet is one desirable means of providing significant improvements to existing facilities. In pursuit of this goal, the mechanical-flush chemical toilet was developed. A prototype was tested extensively and performed satisfactorily. The unique feature of the unit is simplicity; other significant features include low cost, reliable sanitary operation, odor control, and minimum water usage. It is recommended that the toilet be further developed to include a modified tank and an automatic flushing mechanism, and that it then be incorporated into the advanced base functional component system. (Author)